PERANCANGAN SISTEM INFORMASI PELAPORAN POSYANDU LANSIA - Hendra Rohman (Jurnal Manajemen Informasi dan Administrasi Kesehatan, 2018)
The health centre Gondokusuman II was a Yogyakarta Primary Health Centre with two assisted villages, namely Terban and Kotabaru, which has sixteen integrated health post groups for the elderly. Each group of integrated health post sends the results of the patient's health activities once a month to the health centre Gondokusuman II. During this time the reporting used to manage patient data using microsoft excel, but in reporting management found deficiencies namely incomplete reporting, access rights processing elderly patient data can be used by all staff, and in the age column was still filled manually. The purpose of the study was to design a microsoft access 2010 integrated health post based elderly information reporting system in the health centre Nutrition Consultant Unit Gondokusuman II. This study uses a prototype design method as a method of developing management information systems based on microsoft access. The subject of this research was the integrated health post officers of the elderly in the nutrition consultant unit of the health Gondokusuman II. In this study started from the needs of users, applications and information system prototypes that are used as microsoft based desktop access. This prototypes was approved by users, complete filling becomes more complete, access rights can be set, and the age calculation was automatic.Keywords: primary health centre, medical record, electronic